The Unprecedented Movement Control Order (Lockdown) and Factors Associated With the Negative Emotional Symptoms, Happiness, and Work-Life Balance of Malaysian University Students During the Coronavirus Disease (COVID-19) Pandemic - Wan Mohd Yunus, Wan Mohd Azam; Badri, Siti Khadijah Zainal; Panatik, Siti Aisyah; Mukhtar, Firdaus (Frontiers in Psychiatry, 2021)
Background and aims: Malaysia’s Movement Control Order (MCO) or ‘lockdown’ was in place for 6 weeks to curb the spread of COVID-19. Consequently, all universities were forced to temporarily close with abrupt changes to teaching and learning activities. However, there has been a lack of consensus regarding students' actual psychological status and mental health during the MCO implementation. This study investigates the link, state and differences of negative emotional symptoms, happiness, and work-life balance among university students during the COVID-19 pandemic. Methodology: This study recruited 1005 university students across Malaysia. Data was collected online using Qualtrics to measure negative emotional symptoms (The Depression, Anxiety and Stress Scale), happiness (The Oxford Happiness Inventory) and work-life balance (Work-Family Conflict Scale). All data was analysed using SPSS version 25 and AMOS version 26 using T-test, ANOVA, logistic regression analyses and path analysis method. Findings: Findings indicated that 22%, 37.6%, and 37.3% of the university students scored moderate to extremely severe levels of stress, anxiety and depression symptoms respectively. Half scored rather happy or very happy (50%) for happiness levels. Meanwhile, 50.4% and 39.4% scored high to very high levels of work-to-family and family-to-work conflict. Significant differences in stress, anxiety, depression, happiness, work-family conflict, family-work conflict were recorded across different demographic factors. Happiness was found to be a protective factor with a lesser likelihood of experiencing severe stress (OR=.240, 95%CI:.180,.321), anxiety (OR=.336, 95%CI:.273,.414), and depression (OR=.121, 95%CI:.088,.165) with higher happiness levels. Higher score of work-to-family conflict contributes to greater odds of having severe levels of depression (OR=1.453, 95%CI:1.161,1.818). While greater likelihood of developing severe stress (OR=1.46, 95%CI:1.109,1.943) and severe anxiety (OR=95%CI:1.059,1.683) under increasing score of family-to-work conflict. Besides, happiness is found to negatively linked with lower negative emotional symptoms, while work-family conflict is positively linked with higher negative emotional symptoms. Conclusion: Lockdown implementation during the COVID-19 pandemic appears to have a significant impact on university students’ negative emotional symptoms, happiness and work-life balance. Happiness was found to be a protective factor while the state of work-life balance is a risk factor that can predict students’ negative emotional symptoms.